Islamic capital market support in the Indonesian halal industry development: SWOT analysis - Azwar, Azwar (Review of Islamic Social Finance and Entrepreneurship, 2024)
Purpose – This study aims to analyze the strengths, weaknesses, opportunities, and threats as well as strategies for supporting the Islamic capital market in the context of halal industry development in Indonesia. Methodology – This study used a mixed-method approach in the form of a sequential exploratory design with a SWOT analysis technique. Findings – The Indonesian Islamic capital market has strengths in the successful oversubscription of sukuk issuances (both state and corporate) and growth of Islamic educational institutions. However, it has weaknesses owing to limited corporate awareness and public understanding of the market. Opportunities arise from a youthful and educated demographic, whereas challenges involve the complex issuance process and the limited involvement of State-Owned Enterprises (SOEs). Strategic programs such as integration, incentives, value enhancement, and market deepening are recommended to address these aspects and promote the role of the Islamic capital market in the halal industry and Islamic economic development in Indonesia. Implications – This study devises a range of strategic measures aimed at fostering the establishment of a conducive ecosystem that bolsters the Islamic capital market’s role in advancing the halal industry and Islamic economy within Indonesia. Originality – Unlike previous research, which failed to comprehensively investigate and analyze SWOT factors, this study successfully examined and assessed these elements. Furthermore, this study goes beyond the analysis by suggesting strategic approaches to bolster the Islamic capital market’s role in the development of Indonesia’s halal industry.